2006
DOI: 10.1111/j.1747-5457.2006.00199.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring for Fan and Delta Sandstones in the Offshore Falklands Basins

Abstract: Four basins surround the Falkland Islands, but only the North Falkland Basin has been drilled; six wells were drilled there in 1998. Although all six wells encountered good quality sandstones, none of them targeted the basin margins, on what are now thought to be the optimum migration pathways associated with the basin's thick lacustrine source rocks. Subsequently, a 3D seismic survey acquired in 2004 was designed to identify potential basin-margin -derived sandstones entering the basin along transfer zones. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 11 publications
1
19
0
Order By: Relevance
“…It is only with the recent radiometric data summarized here that provides a younger Early Aptian age for the upper age limit of these sandstones, and therefore recalibrates the C. rallus event to a younger, Aptian age. In all other respects, the findings of this paper and others in 'The North Falkland Basin revisited' thematic set build upon and complement the depositional model described by Richards et al (2006).…”
Section: Chronostratigraphysupporting
confidence: 53%
See 1 more Smart Citation
“…It is only with the recent radiometric data summarized here that provides a younger Early Aptian age for the upper age limit of these sandstones, and therefore recalibrates the C. rallus event to a younger, Aptian age. In all other respects, the findings of this paper and others in 'The North Falkland Basin revisited' thematic set build upon and complement the depositional model described by Richards et al (2006).…”
Section: Chronostratigraphysupporting
confidence: 53%
“…Richards et al (2006) suggested that the majority of the coarse clastic input (therefore including the SLMC) into the NFB occurred during the Berriasian-Barremian. Similarly, the biostratigraphic data presented here would also date these sandstones as predominantly not younger than Barremian, based on the C. rallus event described above.…”
Section: Chronostratigraphymentioning
confidence: 99%
“…The middle slope surveyed was entrenched by seven submarine canyons [78]. Pockmarks and other seismic and morphologic evidence of gas/fluids seepage were pervasive throughout the entire survey area and more intense in the southern middle part [80]. Water coral communities associated with those pockmarks could be quite extensive in the study area.…”
Section: Discussionmentioning
confidence: 96%
“…These gas and fluid seepages contributed to the formation of canyons and to the partial detachment of blocks from the canyon walls. Thus, the thermogenic gas responsible for the formation of the identified pockmarks on the middle slope could be deep-seated, probably related to the Falkland Rift Basin, north of the Falkland (Malvinas) Islands [80,81]. The association of gas seepage with deep-water corals has been reported by [82] in pockmarks off Brazil.…”
Section: Geomorphologymentioning
confidence: 91%
“…Until now, five wells found non-43 commercial hydrocarbon shows and only one gas chimney has been reported in this basin, 44 identified by the observation of a diffuse, vertical cone-shaped area in 2D seismic reflection 45 data (Richards et al, 2006). In contrast, within the neighbouring Austral-Magallanes Basin, 46 Thomas (1949) reported the occurrence of numerous gas seeps and one oil seep.…”
mentioning
confidence: 99%